Audio Visual Media Based on Problem Based Learning Water Cycle Topics for Class V Elementary School - I Komang Adi Prayoga; I Gusti Ayu Tri Agustiana (Universitas Pendidikan Ganesha, 2023)
Learning media is used to convey messages to educators and students. The lack of use of technology-based media causes students to experience difficulties in understanding complex science material. This research aims to create audio-visual learning media with a PowerPoint application based on problem-based problem-based learning on the water cycle topic for fifth-grade elementary school students. This research uses the ADDIE model. The data collection methods and instruments used in this research are questionnaires, rating scales, and tests. The subject of this research is a product in the form of audio-visual learning media with a Powtoon application based on problem-based learning on the water cycle. At the same time, the object of development is content validity, practicality, and product effectiveness. The data analysis technique uses qualitative and quantitative descriptive analysis. The research results showed that the level of media validity was in the very good category. The results of the effectiveness test of audio-visual media with the Powtoon application based on Problem-Based Learning show that there is a significant difference between audio-visual learning media and the Powtoon application based on problem-based learning on the topic of the water cycle for the fifth-grade elementary school students on learning outcomes. So, the learning media developed is feasible and effective to improve student learning outcomes. This research implies that teachers can use video media in learning.